2004
DOI: 10.1002/uog.1805
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound with maximal mode rendering: a novel technique for the diagnosis of bilateral or unilateral absence or hypoplasia of nasal bones in second‐trimester screening for Down syndrome

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 19 publications
0
35
0
4
Order By: Relevance
“…trisomy 21 and trisomy 18) and, therefore, careful examination of the skeleton should be carried out in fetuses with missing nasal bones. 3D ultrasound has previously been found to be a useful tool for the diagnosis of absent/hypoplastic nasal bones in fetuses with Down's syndrome [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…trisomy 21 and trisomy 18) and, therefore, careful examination of the skeleton should be carried out in fetuses with missing nasal bones. 3D ultrasound has previously been found to be a useful tool for the diagnosis of absent/hypoplastic nasal bones in fetuses with Down's syndrome [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, questiona-se se a adoção de imagem 3D realmente modifica o desempenho da técnica bidimensional (2D) no rastreio das cromossomopatias, mais notadamente da síndrome de Down [9][10][11] . Vários estudos têm demonstrado maior eficácia do rastreamento da trissomia 21 no primeiro trimestre de gestação ao acrescentar a informação da ausência ou presença ecográfica do osso nasal [12][13][14] .…”
Section: Introductionunclassified
“…The returning echoes are processed by computer program in such a way to give three-dimensional image volume especially of the fetus, and are comparable to CT scan machine image construct. Clinical use of this technology is an area of intense research activity especially in fetal anomaly scanning (Benacerraf et al, 2005;Benoit and Chaoui, 2004;Krakow et al, 2003) but there are also popular uses that have been shown to improve fetal-maternal bonding (Ji et al, 1997) (Tranquart et al, 1999). Images are derived from the higher frequency, especially second harmonic sound, as the ultrasound pulse passes through the body tissue (Muir and Carstensen, 1980;Staritt et al, 1985Staritt et al, , 1986.…”
Section: Principlementioning
confidence: 99%